Sustainable tourism, local and regional kitchens, tastes, and saberes in Peru - Gonzales Vega, Tirso Antonio (2017)
Worldwide and in Latin America small farmers, hunters, pastoralists, and fisherfolk communities contribute between 60 to 70 percent of the total food output (Oxfam, 2011; Altieri & Parviz, 2008). Thus, serving the needs of local, regional and global kitchens. The mixture of taste, saberes, and local and regional kitchens nests in the local and regional bio-cultural diversity ́s archipelago. Local and regional kitchens can be observed and positioned strategically as an emerging identity stream closely linked to the conscious regeneration of the bio-cultural-spiritual landscape, and as a part of a sustainable food proposal. From a panoramic view, this article reflects on key links of a chain that constitutes an alternative paradigm; and contributes to enhance local and regional kitchens multidimensionality with relation to culture, ecology and environment. It concludes that, a sustainable tourism-kitchen; environment-food strategy is possible due to the strategic centrality of small agri-cultures and their unique ancient bio-cultural-eco-spiritual potential. Small farming can contribute realistically to resolve critical problems of malnourishment, food safety and quality, and the regeneration of the local and regional bio-cultural landscape. That would potentiate, expand, and add value to sustainable tourism in Peru.